2020
DOI: 10.1002/ps.6040
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450‐mediated herbicide metabolism in plants: current understanding and prospects

Abstract: Cytochrome P450s (P450s) have been at the center of herbicide metabolism research as a result of their ability to endow selectivity in crops and resistance in weeds. In the last 20 years, ≈30 P450s from diverse plant species have been revealed to possess herbicide-metabolizing function, some of which were demonstrated to play a key role in plant herbicide sensitivity. Recent research even demonstrated that some P450s from crops and weeds metabolize numerous herbicides from various chemical backbones, which hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 79 publications
0
93
0
Order By: Relevance
“…A similar dual functionality has been observed for promiscuous monoterpenol metabolizing CYP76s that confer a tolerance to another class of herbicides, the phenylureas (H€ ofer et al, 2014). In this light, it is striking that members of the CYP81A subfamily have been recently shown to metabolize a broad range of herbicides, thereby conferring herbicide resistance to monocotyledonous weeds (Dimaano and Iwakami, 2020;Han et al, 2020), while CYP81As from maize were demonstrated to catalyze diverse oxidation reactions on acidic sesquiterpenes to form zealexin antibiotics (Ding et al, 2020).…”
Section: Cyp Promiscuity As a Seed For New Functionsmentioning
confidence: 99%
“…A similar dual functionality has been observed for promiscuous monoterpenol metabolizing CYP76s that confer a tolerance to another class of herbicides, the phenylureas (H€ ofer et al, 2014). In this light, it is striking that members of the CYP81A subfamily have been recently shown to metabolize a broad range of herbicides, thereby conferring herbicide resistance to monocotyledonous weeds (Dimaano and Iwakami, 2020;Han et al, 2020), while CYP81As from maize were demonstrated to catalyze diverse oxidation reactions on acidic sesquiterpenes to form zealexin antibiotics (Ding et al, 2020).…”
Section: Cyp Promiscuity As a Seed For New Functionsmentioning
confidence: 99%
“…Plant P450 proteins are encoded by large, diverse multigene families consisting of c . 350 genes in rice and 250 genes in Arabidopsis , and are involved in numerous processes such as secondary product biosynthesis, fatty acid metabolism, hormone homeostasis and xenobiotic detoxification (Nelson et al ., 2004; Paquette et al ., 2009; Mizutani & Ohta, 2010; Schuler, 2015; Dimaano & Iwakami, 2021). Phase II metabolic reactions are catalyzed by glutathione S ‐transferases (GSTs; EC 2.5.1.18) and uridine diphosphate‐dependent glycosyltransferases, forming GSH conjugates and glucose conjugates, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There are four CYP81A genes annotated in the whole genome of rice, and one of them ( CYP81A6 ) plays a key role in the tolerance of rice to multiple herbicides, such as sulfonylureas and bentazone 12 . The CYP81A P450s often metabolize a variety of herbicides, although some only metabolize a small number or no herbicides 13 . Thus, we hypothesized that the CYP81A genes in rice may explain the differential clomazone sensitivity between short/medium‐ and long‐grain cultivars.…”
Section: Introductionmentioning
confidence: 99%